A Comparative study of cadastre 2014 and the Zimbabwean cadastral system - Mapamula, Robert T.; Paradzayi, Charles; Kurwakumire, Edward (2017)
The global trend in land information management over the last two decades has been to migrate from paper to computer based information systems. Notable concepts in this regard are: Cadastre 2014, Core Cadastral Domain Model, Land Administration Domain Model (LADM) and subsequent related works. In Zimbabwe, although some concepts in these guidelines manifest in most recent policy documents such as the Zimbabwe Agenda for Sustainable Socio-Economic Transformation (ZimAsset), there has been no deliberate effort to implement them in a holistic and structured manner. This has resulted in fragmented solutions that have failed to meet the requirements of modern land information systems. A case study approach was adopted to gather information from stakeholders working within the Department of the Surveyor General, Deeds Registry, Local Planning Authorities and also including private practitioners involved in the cadastral system. In order to document and describe the existing cadastral framework in the country, an investigation through review of the relevant scholarly articles, policy documents and government reports was carried out, followed by interviews and questionnaires targeted at the major stakeholders. The underlying concepts of the cadastral framework in terms of its operation and workflows were investigated and compared with the Cadastre 2014 conceptual framework. Results indicated that no significant strides have been made in Zimbabwe towards implementing the six statements of Cadastre 2014 and other related best practice standards. This paper is useful as background for any research that will be done on the Zimbabwean cadastre. However, currently there is some momentum towards realisation of new tenure arrangements, review of land survey records and the capturing of cadastral information in a digital environment. This paper contributes to the body of knowledge of cadastral systems in the Zimbabwean context and in the world at large.